THE EXPERIENCE OF INTRODUCTION AND RELIABILITY SUPPORT OF SULPHUR HEXAFLUORIDE CIRCUIT BREAKERS IN OPERATION CONDITIONS - Kytin, Vasyl; Rybanenko, Olexandre; Mysenko, Sergix (Scientific Works of Vinnytsia National Technical University, 2015)
The paper considers the results of the analysis, performed after introduction of sulphur hexafluoride switches at the enterprises of South-West Energy System (SWES) and improvement of methods and means of technical diagnostics of high-voltage switches in operation conditions. REFERENCES 1. Нормативний документ мінпаливенерго України. Норми випробування електрообладнання. СОУ-Н ЕЕ 20.302: Київ. 2007. – 271 c. 2. Тимашова Л. В. Анализ повреждаемости выключателей 110-750 кВ / Л. В. Тимашова, И. Л. Шлейфман, И. А. Назаров / Материалы V международной научно-техническай конференции «Высоковольтное коммутационное оборудование». Москва, 2009. – 200 с. 3. Кутин В. М. Диагностирование электрооборудования электрических систем: Учеб. Пособие / В. М. Кутин, В. И. Брейтбурд. – К.: УМК ВО, 1991. – 104 с. 4. Кутін В. М. Вдосконалення методів діагностування високовольтних вимикачів / В. М. Кутін, О. Є. Рубаненко, С. В. Мисенко // Вісник Вінницького політехнічного інституту. – 2012. – № 1. – С. 109 – 113. 5. Справочник по проектированию электрических сетей / под. ред. Д. Л. Файбисовича.  3-е изд., перераб. и доп.  М.: ЭНАС, 2009.  392 с. 6. Справочник по проектированию электрических сетей / под. ред. Д. Л. Файбисовича.  М.: Изд-во НЦ ЭНАС, 2005.  320 с. 7. Неклепаев Б. Н. Электрическая часть электростанций и подстанций: Справочные материалы для курсового и дипломного проектирования. / Б. Н. Неклепаев, И. П. Крючков / Учеб. Пособие для вузов. – 4-е изд., перераб. и доп.  М.: Энергоатомиздат, 1989.  608 с.